Electric circuits - Balabanian, Norman (McGraw-Hill, 1994)
This book about the fundamental laws; Two-terminal components; Simple dissipative structures; Multiterminal components; Analysis of dissipative circuits; Signals and first-order circuits; Second-order circuits; Inductive coupling and transformers; Frequency response and resonance; The complex frequency and network functions; Nonsinusoidal periodic excitations; Laplace transforms and the complete response to arbitrary waveforms.